Regional disparities and within-country inequality in the European Union - Roberto Ezcurra (Revista de Economía Mundial, 2019)
This paper examines spatial disparities in terms of development within  EU countries, using data for 272 regions in the current 28 member states over the period 1996-2010. The analysis carried out confirms that within-country inequality is an important component of overall inequality across European regions. Indeed, regional inequality increased in most EU countries throughout the study period. The results also underline the relevance of national development for within-country inequality, although the relationship is not linear. The advances in national GDP per capita first increase regional inequality. However, beyond a threshold level, the link turns from positive to negative and richer countries tend to experience lower levels of regional inequality. Moreover, the opening of national borders to international markets is associated with higher regional inequality in the EU countries. At the same time, countries with better quality of government have lower levels of regional inequality. These results do not depend on the specific measure used to quantify  the magnitude of regional disparities within the sample countries.